The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12576-020-00735-4
|View full text |Cite
|
Sign up to set email alerts
|

Paired mechanical and electrical acupuncture of neurogenic spots induces opioid-mediated suppression of hypertension in rats

Abstract: While our recent studies have suggested that effective acupoints display neurogenic inflammation and can be identified as neurogenic spots (Neuro-Sps), the optimal stimulation conditions and the underlying mechanisms remain uncharacterized. We developed a combined mechano-electrical acupuncture device (MEA) and examined the effects of acupuncture at Neuro-Sps on systolic blood pressure (BP) in a rat model of immobilization-induced hypertension (IMH) and the mediation of endogenous opioid systems in its effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…The rVLM plays an important role in regulating sympathetic activity associated with cardiovascular function (Sved et al, 2003) and stimulation of the PC6 acupoint significantly attenuates visceral sympathoexcitatory reflex responses through activation of opioid receptors in the rVLM (Chao et al, 1999;Li et al, 2002;Zhou et al, 2005a). Consistent with previous studies (Shin et al, 2020;Zhou et al, 2005b), the present study revealed that stimulation of Neuro-Sps near the wrist increased rVLM neuronal activity in IMH rats, which was prevented by local injection of SP receptor antagonist into Neuro-Sps. This suggests that locally released SP is linked with rVLM neuronal activity following acupuncture.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rVLM plays an important role in regulating sympathetic activity associated with cardiovascular function (Sved et al, 2003) and stimulation of the PC6 acupoint significantly attenuates visceral sympathoexcitatory reflex responses through activation of opioid receptors in the rVLM (Chao et al, 1999;Li et al, 2002;Zhou et al, 2005a). Consistent with previous studies (Shin et al, 2020;Zhou et al, 2005b), the present study revealed that stimulation of Neuro-Sps near the wrist increased rVLM neuronal activity in IMH rats, which was prevented by local injection of SP receptor antagonist into Neuro-Sps. This suggests that locally released SP is linked with rVLM neuronal activity following acupuncture.…”
Section: Discussionsupporting
confidence: 91%
“…Single-unit discharges of rVLM neurons were recorded in anesthetized rats, as described previously (Shin et al, 2020). In brief, 1 h after immobilization with a cone-shaped polyethylene bag, rats were anesthetized with an intraperitoneal injection of urethane (1.5 g/ kg).…”
Section: In Vivo Extracellular Single-unit Recordings Of Rostral Ventrolateral Medulla (Rvlm) Neuronsmentioning
confidence: 99%
“…The present study showed that stimulation of neurogenic spots near the wrist activated rVLM and vlPAG. This finding is consistent with previous studies showing that stimulation of neurogenic spots or electroacupuncture at acupoints near the wrist induced c-Fos expression in the rVLM and PAG, 25 , 29 central sites for the regulation of blood pressure. 30 , 31 A previous study demonstrated that electrical stimulation of the median nerve over the wrist activates the arcuate nucleus, thereby regulating blood pressure via cardiovascular sympathetic neurons in the vlPAG and rVLM sites.…”
Section: Discussionsupporting
confidence: 93%
“… 4 , 22 Our previous studies have shown scientific evidence regarding the close relationship between traditional acupoints and neurogenic inflammatory spots. 4 , 8 , 9 , 23 , 24 , 25 In brief, most neurogenic inflammatory spots are found in the same anatomical location as traditional acupoints and reveal the same physiological features as acupoints (i.e., high electrical conductance or mechanical hypersensitivity). We have suggested that traditional acupoints may be identical to neurogenic inflammatory spots occurring on the skin that are associated with visceral disorders.…”
Section: Discussionmentioning
confidence: 99%
“…So far, previous studies have focused on the relationship between the stimulus frequency and BP response in aVNS, and other studies have focused on stimulation methods and quantitative comparisons of changes in BP for clinical translation lacking the frequency-dependent temporal course of BP changes [9,23,37]. The results of the present study suggest that the antihypertensive response time of aVNS can be predicted with the NTS activation time according to stimulation frequency.…”
Section: Analysis Of Avnsmentioning
confidence: 56%